Wind Industry and Energetic Transition. Potential For Latin America - Zepeda Cancino, Rubén Manuel (2021)
Brazil, Mexico and Uruguay have adopted wind energy as a means to fight climate change. However, their experiences are different and insufficiently documented. This paper analyzes the advantages and disadvantages of the wind industry in light of its future expansion in Latin America. The methodology consists of the systematization and analysis of literature written in Spanish, Portuguese and English. Four advantages and five disadvantages were identified. The advantages are wind energy’s reduced carbon footprint, low production costs, the potential for job creation and income from land rentals, while the disadvantages are possible vegetation loss, impact on birds and water sources, oil and waste contamination and health damage. The challenges for public policy are: supporting research on the socioenvironmental impacts of the wind industry and designing tools for their mitigation; developing a full supply chain of materials through technological innovation; distributing the benefits of wind energy equally among the local population, and prioritizing public needs of electricity above the interest of the private sector. If these challenges are not fully met, wind energy projects will be part of a hegemonic structure that claims to solve the problems created by climate change, while in fact continuing to use an extractivist logic, incapable of benefitting people.